A Pilot Study Comparing Sex Trafficking Indicators Exhibited by Adult and Minor Service Populations. Issue 2 (3rd April 2023) - Nichols, Andrea J.; Cox, Ashley
ABSTRACT: Indicators of sex trafficking are widely disseminated by organizations in the criminal justice, social service, healthcare, and community sectors. Drawing from a larger pilot study examining survey responses of providers working with sex trafficking survivors ( N = 86), the present study specifically examines providers' observations of 62 sex trafficking indicators comparing minor and adult service populations ( n = 47) in a Midwestern metropolitan area. Respondents indicated how commonly such indicators appeared among their service populations. Robust MANOVA identified a significant effect of age group on five out of the six domains of indicators. Univariate Mann-Whitney tests showed that overall there were few differences in observed indicators comparing adults and minors, yet participants reported significant differences for several mental health indicators. Median responses similarly showed overlap as well as differences in observed indicators among adult and minor service populations. Implications for further research examining indicators with the aim of improving identification, screening questions, and practice are provided.